The comparative study of aerosol filtration by electrospun polyamide, polyvinyl acetate, polyacrylonitrile and cellulose acetate nanofiber media. (February 2016) - Matulevicius, Jonas; Kliucininkas, Linas; Prasauskas, Tadas; Buivydiene, Dalia; Martuzevicius, Dainius
Abstract: Nanofiber media produced from different polymers via electrospinning were examined for the removal of aerosol particles from the air flow. The polymeric materials used as a filter media included polyamides 6 (PA6) and 6/6 (PA6/6), polyvinyl acetate (PVAc), polyacrylonitrile (PAN), and cellulose acetate (CA). The comparative filtration performance of the single-ply and multi-ply nanofiber media mats was evaluated. The measurements of filtration efficiency and estimation of quality factors (QF) were performed for monodisperse 100 and 300 nm polystyrene latex and polydisperse NaCl particles. The results revealed that PVAc nanofiber media filter (PVAc_60) due the unique morphology of beaded nanofibers combined the highest QF and the high filtration efficiency: 0.055 Pa −1 (98.79%) for 100 nm particles and 0.042 Pa −1 (96.79%) for 300 nm particles accordingly. The PAN nanofiber media also showed relatively high filtration properties, while other nanofiber media (PA and CA) with high quality factors did not exceed filtration efficiency of 91%. The comparison of one-ply and multi-ply nanofiber media, characterized by lower basis weight, showed that multi-ply structures only slightly increase filtration properties for 100 and 300 nm particles, in some cases worsening filtration properties. Graphical abstract: Highlights: Electrospinning of PA6/6, PA6, PVAc, PAN and CA polymers for air filtration application. PVAc and PAN nanofiber media exhibited the highest filtration performance. The selected fiber media combined high filtration efficiency with high quality factor. Multi-ply nanofiber mats marginally increase filtration quality factor.